2021
DOI: 10.1136/bmjopen-2020-047513
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ (GPs) understanding and views on breast density in Australia: a qualitative interview study

Abstract: ObjectivesTo understand general practitioners’ (GPs’) awareness and knowledge of mammographic breast density (BD) and their perspectives around information and potential notification of BD for women.DesignQualitative study using semistructured telephone interviews. Interviews were audiorecorded, transcribed and analysed using framework analysis.SettingAustralia.ParticipantsAustralian GPs (n=30).ResultsGPs had limited knowledge of BD and little experience discussing BD with women. There were mixed views on noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Regardless, even among this group of GPs who had self-selected to participate in the current study and had a higher level of awareness or experiences with breast-density-related issues, the interest and need for further education and training is clear. This is in line with our earlier qualitative study findings [ 16 ]. This highlights the need for widespread education campaigns, especially if breast density notification is to be introduced through BreastScreen programs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regardless, even among this group of GPs who had self-selected to participate in the current study and had a higher level of awareness or experiences with breast-density-related issues, the interest and need for further education and training is clear. This is in line with our earlier qualitative study findings [ 16 ]. This highlights the need for widespread education campaigns, especially if breast density notification is to be introduced through BreastScreen programs.…”
Section: Discussionsupporting
confidence: 94%
“…Nickel et al previously conducted a qualitative study into the views and perception of Australian GPs regarding breast density and potential notification [ 16 ]. The findings from this study pointed to GPs’ limited knowledge about breast density and mixed views towards notification, especially when clear guidelines in managing breast density are lacking [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study from the state of Western Australia where they currently notify women of their breast density found that half of women notified consulted or intended to consult with their general practitioner (GP), and of those, 50% were referred for supplemental screening and 20% reported having an ultrasound [ 24 ]. Of concern, however, is that important gaps still exist in GP knowledge about breast density and confidence in having discussions with women about the implications [ 25 , 26 ], and the current lack of evidence-based management guidelines for GPs.…”
Section: Discussionmentioning
confidence: 99%
“…38 Previous studies have shown that GPs in Australia and primary care practitioners in the US had limited knowledge about breast density, were uncertain about how to manage care for women with dense breasts, and needed support and training. 39,40 With an expected increase in GP consultations related to breast density and cancer risk if notification is introduced, it will be crucial to ensure GPs have the knowledge and resources to counsel individuals about breast density and the pros and cons of supplemental screening, including in relation to psychological well-being. Informed and shared decision-making models based on evidence, patient values and goals, and joint decisions may help to reduce worries and other adverse psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%